CLASSROOM MANAGEMENT: LEARNERS’ MOTIVATION AND ORGANIZE THE LEARNING ENVIRONMENT OF PAI - Sulaiman, Sulaiman (UIN Ar-Raniry, 2017)
Classroom management is the key to success and improves the quality of PAI learning in the classroom. Learners are potential classes who can be utilized through effective classroom management. Teachers are required to have classroom management skills to optimize the PAI learning process in the classroom effectively. Conducive, challenging and inspiring classroom situations can develop PAI learning motivation. This is the positive implication of effective classroom management on PAI learning.